Who Do Unions Target? Unionization over the Life-Cycle of U.S. Businesses - Emin Dinlersoz; Jeremy Greenwood; Henry R. Hyatt (Institute for the Study of Labor (IZA), 2014)
What type of businesses do unions target for organizing? A dynamic model of the union organizing process is constructed to answer this question. A union monitors establishments in an industry to learn about their productivity and decides which ones to organize and when. An establishment becomes unionized if the union targets it for organizing and wins the union certification election. The model predicts two main selection effects: unions secure elections in larger and more productive establishments early in their life-cycles, and among the establishments that experience an election, unions are more likely to win in smaller and less productive ones. These predictions find support in union certification election data for 1977-2007 matched with data on establishment characteristics. Other empirical regularities pertaining to union organizing are also documented.
Keywords: J5; J50; J51; L11; L23; L25; L6; D24; D21; 330; unionization; union organizing; union certification election; diffusion of unionization; Bayesian learning; productivity